IMPROVING THE QUALITY OF LEARNING IN IMMIGRATION POLYTECHNICS THROUGH IMMIGRATION MANAGEMENT INFORMATION SYSTEM FACILITIES DIRECTORATE GENERAL OF IMMIGRATION - Fakhri Hafiz-AM (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
Immigration Polytechnic is an official university under the Ministry of Law and Human Rights wich produces immigration cadres who have integrity and intellectuality to carry out their duties as immigration officer. The Human Resources Development Agency is a forum for produce student from the Immigration Polytechnic. On the other side, Directorate General of Immigration has a system called the Sistem Informasi Manajemen Keimigrasian (SIMKIM). The problem that will be to describe how the learning process at the Immigration Polytechnic is currently and how to utilize the existing system to support learning at the Immigration Polytechnic. The application of the research method used is descriptive qualitative research method, namely by explaining or describing an object of research by means of observation and interviews with related sources. Based on the research results, it can be concluded that the learning process at the Immigration Polytechnic goes through several stages and also uses Teaching, Training, and Nurturing patterns that can improve the quality of Cadets. And also the Immigration Polytechnic has utilized several systems that are very helpful for learning, including Sistem Pengaduan Taruna (SIPENA), Sistem Informasi Akademik (SIAKAD), Electronic Learning Immigration System (ELIPS), dan juga Immigration Exam (IM-EXAM).